2020
DOI: 10.1109/access.2020.2992567
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Human Balance Control by Calf Muscle Activation Modelling

Abstract: The natural neuromuscular model has greatly inspired the development of control mechanisms in addressing the uncertainty challenges in robotic systems. Although the underpinning neural reaction of posture control remains unknown, recent studies suggest that muscle activation driven by the nervous system plays a key role in human postural responses to environmental disturbance. Given that the human calf is mainly formed by two muscles, this paper presents an integrated calf control model with the two comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The human natural CNS includes two prime structures: spinal cord and the brain, which can be regarded as a hierarchical control structure [22]. The brain is usually referred to as an advanced central nervous system (ACNS), and the spinal cord is often known as the lower central nervous system (LCNS).…”
Section: Neural Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The human natural CNS includes two prime structures: spinal cord and the brain, which can be regarded as a hierarchical control structure [22]. The brain is usually referred to as an advanced central nervous system (ACNS), and the spinal cord is often known as the lower central nervous system (LCNS).…”
Section: Neural Controllermentioning
confidence: 99%
“…Case C: The exoskeleton is controlled by the proposed virtual neuromuscular control method. With reference to the important conclusion of biomedical research on the human ankle calf muscle [22], which provides the guidance for controller parameters setting, the virtual muscle mechanical model parameters in the experiment are shown in Table 2, and the parameters of the neural control are shown in Table 3.…”
Section: Experiments Conditionmentioning
confidence: 99%
“…Mirvakili et al [1] analyzed the material, structure, and driving mechanism of artificial muscle and found that the performance indicators of artificial muscle actuators, such as force, power, cost, lifecycle, and efficiency, exceeded those of biological muscle. Yin et al [2] simulated an artificial muscle calf joint model designed by a natural neuromuscular model and showed that it successfully performed over 92% of the muscle activation that was naturally made by human participants. Terryn et al [3] applied the Diels-Alder polymer to artificial muscle, giving soft robots not only bionic flexibility for absorbing shock and preventing body damage but also a certain degree of self-healing ability.…”
Section: Introductionmentioning
confidence: 99%
“…ese abilities of human beings have provided the best guidance to advance the design of robotic controllers. e authors in [11] attempted to build the virtual neuromuscular model for robotic control. is approach can generate human-like diverse and robust locomotion behaviors.…”
Section: Introductionmentioning
confidence: 99%